Is It Still Double Edged? Not for University Students’ Development of Moral Reasoning and Video Game Play - Hodge, Sarah E.; Taylor, Jacqui; McAlaney, John (Frontiers in Psychology, 2020)
Previous research with video game play and moral development with adolescents, found both positive and negative relationships. This study aimed to extend this research to explore moral development and video game play with University students. One hundred and thirty-five undergraduate students (M = 20.29 SD = 2.70) took part in an online survey. The results suggested higher moral reasoning for participants who described themselves as gamers and those which do not players, compared to the those who play but do not identify as gamers. It was suggested that males had higher moral scores and more mature reasoning than females. The results of a regression analysis suggested that there were no significant predictors for moral development from either game play or the demographic variables. The findings suggest that moral development could be less influenced by sex, age, and video game play factors such as video game content and amount of game play, than was previously thought.